Finite element analysis of Kirschner wire fixation for lateral condyle fracture in children in the sagittal plane - Huanan Bai; Huanan Bai; Qingda Lu; Xiaoju Liang; Xiaoming Wang; Yating Yang; Huan Wang; Jiaju Wang; Qiang Jie (Frontiers Media S.A., 2023)
ObjectiveThis study aims to find the optimal arrangement of the Kirschner wire (K-wire) in the sagittal plane for fixation of a pediatric lateral condylar humeral fracture (Milch type II) by using finite element analysis (FEA).MethodsA model of lateral condyle fracture in a 6-year-old boy was developed, and an XYZ coordinate system was established based on this model. The YZ plane was defined as the sagittal plane to investigate the impact of the angle formed by the first and second K-wires on stability. Two configurations were studied for each angle: parallel and divergent. Evaluation indicators included the maximum displacement of the fracture fragment and the maximum von Mises stress in the pins and bone.ResultsThe model with a −60° angle showed the best performance in both evaluation indicators. The parallel and divergent pin configurations had different performances in each group. The displacement results for negative angles were similar, and this result was better than those for positive angles.ConclusionWe successfully created a model of pediatric lateral condyle humerus fracture (Milch type II) and performed K-wire fixation with varying sagittal plane configurations, combined with FEA. Our findings demonstrate that the angle of −60° between the two pins in the sagittal plane provided the highest level of stability, with divergent configurations proving superior to parallel pinning at this angle.